Perancangan Kembali UI/UX Website Cantique Property Sebagai Media Promosi Dengan Metode User-Centered Design - Rifqi, Eriz; Haq, Endi Sailul; Wibowo, Galih Hendra; Yusuf, Dianni; Rini, Eka Mistiko (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
In the modern era that continues to develop, websites have become a common part for promotional media, transactions, and obtaining information on the buying and selling transaction process. UI/UX improvements on the Cantique Property website are very important in building a company's image and improving user experience. By using the User-Centered Design (UCD) approach, the main focus is to facilitate access to information and create an impressive experience for users. Then using the System Usability Scale (SUS) method using a questionnaire distributed via Google Forms by applying SUS questionnaire questions to test the usability of a system. The results of the study obtained before the SUS redesign were obtained, namely 44% where the grade scale was at F with a poor indicator. Then after the redesign, the SUS value obtained increased to 80% which was at grade scale A with a good indicator. so it can be concluded that the design improvements made brought an increase in score of around 36%, so that this proves that testing with SUS in this study was successful and the new design was well received by website users.